2019
DOI: 10.20902/ijctr.2019.120137
|View full text |Cite
|
Sign up to set email alerts
|

A review of Drying Technologies for Refuse Derived Fuel (RDF) and Possible Implementation for Cement Industry

Abstract: Refused-Derived Fuel (RDF) in global energy demand plants has risen over the past decades as a sustainable secondary supply of energy resources. Food waste as a significant fraction of municipal solid waste (MSW) has a great potential for energy production especially in developing country such as Indonesia. To date, many industries focus on drying technologies development for utilization of food waste for energy conversion. Lowering moisture content of food waste is essential to improve RDF heating value (LHV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Their results showed that the daily efficiency of the solar air heater considered with 800 baffles was 29.91-51.69% higher than that of the conventional one. Zamrudy, W., et al (2019) reviewed different RDF drying technologies for subsequent use of RDF in the cement industry. It can be concluded from their review that the main drying equipment for RDF include a conveyor belt dryer, Torbed reactor, screw conveyor, indirect rotary dryer, and direct rotary drum dryer.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the daily efficiency of the solar air heater considered with 800 baffles was 29.91-51.69% higher than that of the conventional one. Zamrudy, W., et al (2019) reviewed different RDF drying technologies for subsequent use of RDF in the cement industry. It can be concluded from their review that the main drying equipment for RDF include a conveyor belt dryer, Torbed reactor, screw conveyor, indirect rotary dryer, and direct rotary drum dryer.…”
Section: Introductionmentioning
confidence: 99%